EVALUASI KINERJA KEUANGAN BERDASARKAN METODE VALUE FOR MONEY PADA PENGELOLAAN APBD KOTA MAKASSAR - Andi Asti Handayani; Tuti Supatminingsih (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Makassar City, as one of the metropolitan cities in Eastern Indonesia, has a great responsibility to ensure financial management that supports sustainable development and optimal public services. This study evaluates the financial performance of Makassar City in 2021–2023 based on the Value for Money principle, namely economic aspects, efficiency, and effectiveness. The research method is quantitative descriptive and secondary data sources in the form of the Budget Realization Report (LRA) of Makassar City regional revenue and expenditure downloaded from the official website of the Makassar City Government. The economic ratio analysis shows that budget management was categorized as economical in 2021 and 2022, and fairly economical in 2023. The efficiency ratio was categorized as less efficient in 2021 and 2022, and not efficient in 2023. Meanwhile, the effectiveness ratio was highly effective in 2021 and fairly effective in both 2022 and 2023. These findings indicate that although Makassar City's budget management was relatively frugal in the first two years, efficiency and effectiveness declined in the third year.